Gambaran Self Compassion pada Mahasiswa Semester 7 Program Studi Pendidikan Dokter Fakultas Kedokteran Universitas Sam Ratulangi - Virene L. Nayoan; Lydia E. V. David; Jehosua S. V. Sinolungan (Medical Scope Journal, 2023)
Abstract: Medical school demands the medical students to be competent in their education, therefore, various academic responsibility can become a source of pressure or stressors for the students. Stress can be overcome when a person has self-kindness, common humanity, and mindfulness. These are the components of self-compassion. This study aimed to obtain the description of self-compassion among students of seventh semester (final semester), Faculty of Medicine of Sam Ratulangi University. This was a descriptive and quantitative study. Samples were taken using purposive sampling technique and 132 respondents were involved in this study. Questionnaires on Indonesian adaptation of the Self Compassion Scale questionnaire with the Likert model were distributed to the respondents. The results showed that based on the level of self-compassion, 92 students (70%) had moderate level of self-compassion, 36 students (27%) had high level of self-compassion, and four students (3%) had low level of self-compassion. Common humanity aspect was in the high category. Self-kindness, self-judgment, isolation, mindfulness, and over-identification aspects were in the moderate category. In conclusion, the average level of self-compassion in students of seventh semester, Faculty of Medicine of Sam Ratulangi University are at moderate level. Keywords: self compassion; final year medical students; academic responsibility; stress   Abstrak: Jurusan kedokteran menuntut mahasiswa kedokteran agar kompeten dalam pendidikannya sehingga berbagai tuntutan akademik dapat menjadi sumber tekanan atau stresor bagi mahasiswa. Stresor dapat dihadapi ketika seseorang mempunyai self-kindness, common humanity, dan mindfulness. Ketiga hal tersebut merupakan aspek dari self compassion. Penelitian bertujuan untuk mengetahui gambaran self compassion pada mahasiswa semester 7 (semester akhir) Program Studi Pendidikan Dokter Fakultas Kedokteran Universitas Sam Ratulangi. Penelitian menggunakan metode kuantitatif deskriptif dengan membagikan kuesioner Skala Welas Diri (SWD) adaptasi Bahasa Indonesia dari Self Compassion Scale (SCS) model Likert. Sampel diambil dengan teknik purposive sampling dan terkumpul sebanyak 132 responden. Hasil penelitian memperlihatkan bahwa sebanyak 92 responden (70%) memiliki tingkat self compassion sedang, 36 responden (27%) memiliki tingkat self compassion tinggi, dan empat responden (3%) memiliki tingkat self compassion rendah. Aspek kemanusiaan universal berada dalam kategori tinggi. Aspek mengasihi diri, menghakimi diri, isolasi, kewawasan, dan overidentifikasi berada dalam kategori sedang. Simpulan penelitian ini ialah rerata tingkat self compassion pada mahasiswa Semester 7 Program Studi Pendidikan Dokter Fakultas Kedokteran Universitas Sam Ratulangi berada pada tingkat sedang. Kata kunci: self compassion; mahasiswa kedokteran semester akhir; tuntutan akademik; stres